1994
DOI: 10.1063/1.357572
|View full text |Cite
|
Sign up to set email alerts
|

The use of graded InGaAs layers and patterned substrates to remove threading dislocations from GaAs on Si

Abstract: We have investigated threading dislocation (I'D) removal from GaAs films on Si by introduction of additional InGaAs graded strain layers in combination with growth on patterned substrates. The substrate patterns consisted of mesas with lo-34 ,wm widths. The mesa sidewalls were either overhanging (concave), leading to free sidewalls for the film on the mesas, or outward sloping (convex) sidewalls with (111) orientation. The dislocation structure was studied using transmission electron microscopy. It was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…From the RSM data shown in Fig. In addition, the previous report indicated that the strain in the epi-layer can exerted a net force on the dislocation, and the dislocation could be bent and terminated at an epilayer edge, without threading through the epilayer to the top surface of the epi-layer [15]. In addition, the reciprocal lattice points of AlGaN and GaN were lined up at the same Q x position, i.e.…”
Section: Discussionmentioning
confidence: 70%
“…From the RSM data shown in Fig. In addition, the previous report indicated that the strain in the epi-layer can exerted a net force on the dislocation, and the dislocation could be bent and terminated at an epilayer edge, without threading through the epilayer to the top surface of the epi-layer [15]. In addition, the reciprocal lattice points of AlGaN and GaN were lined up at the same Q x position, i.e.…”
Section: Discussionmentioning
confidence: 70%
“…However, the TD density described above is high for device applications. The reported TD density of the previously mentioned GaAs layer on the Si substrate 6) was 7 Â 10 8 cm À2 , which is a typical value for as-grown layers using two-step growth. 7) The TD density of an InGaAs layer on a Si substrate might decrease if the TD density of a GaAs layer on a Si substrate is lowered using the reported methods such as thermal cyclic annealing (TCA) or a strained superlattice.…”
Section: Introductionmentioning
confidence: 72%
“…5) Reduction of the TD density to the order of 10 7 cm À2 was achieved in InGaAs layers on GaAscovered Si substrates with graded buffer layers using molecular beam epitaxy. 6) This achievement suggests that InGaAs layers with low TD densities can be grown on high-quality GaAs layers on Si substrates. Furthermore, the graded layer is attractive because it allows the variation of the In composition of the InGaAs layer to a desired value.…”
Section: Introductionmentioning
confidence: 99%
“…Step-graded buffers have been investigated in a number of material systems including In x Ga 1Àx As [27,28,[66][67][68][69], In x Al 1Àx As [24,39,68,[70][71][72][73][74][75][76][77][78][79][80], In x Al y Ga 1ÀxÀy As [19,35,80], and Al x Ga 1Àx Sb y As 1Ày [52,81] on GaAs (001) substrates, InAs y P 1Ày [29,[82][83][84] on InP (001), and In x Al 1Àx Sb [85] on GaSb (001).…”
Section: Step-graded Buffer Layersmentioning
confidence: 99%